2018
DOI: 10.1177/0049475518813792
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous use of two rapid diagnostic tests for the diagnosis of Chagas disease

Abstract: The sensitivity of rapid diagnostic tests (RDT) for Chagas disease is not great enough for their single use. The aim of this paper was to evaluate the performance of two RDTs for Chagas disease, used simultaneously. Two different RDTs (A and B) were performed in 64 and 42 serum samples that were negative and positive, respectively, by conventional serological techniques. Validity and reliability of both tests were evaluated individually and simultaneously. Sensitivity was 90.5% and 97.6%, and specificity was 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 9 publications
2
30
0
Order By: Relevance
“…We must point out that the accuracy parameters of both the SD and WL tests were lower than those indicated by the manufacturers, as already evidenced in other studies (1, [8][9][10][11][12][13][14][15][16][17][18]27).…”
Section: Downloaded Frommentioning
confidence: 58%
See 2 more Smart Citations
“…We must point out that the accuracy parameters of both the SD and WL tests were lower than those indicated by the manufacturers, as already evidenced in other studies (1, [8][9][10][11][12][13][14][15][16][17][18]27).…”
Section: Downloaded Frommentioning
confidence: 58%
“…The field evaluation of the RDTs SD and WL showed that these tests had higher sensitivity and specificity than other ChD RDTs evaluated previously in different countries and using different samples (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). When these RDTs were performed with serum samples, they on October 29, 2020 by guest http://jcm.asm.org/ Downloaded from showed a sensitivity of about 96% to 100% (13,14,18,19), but when they were performed with whole blood samples, their sensitivity decreased between to 96 to 62.5% (15,18).…”
Section: Downloaded Frommentioning
confidence: 80%
See 1 more Smart Citation
“…Various studies have previously described they can provide very good sensitivity and specificity, even working with tiny volumes of whole blood [1922]. Furthermore, the combined use of two RDTs has already been suggested as a substitute of the current algorithm based on conventional serological methods [19, 23]. In the present study we demonstrate that the field use of RDTs by mobile teams could indeed substitute the use of conventional tests in the highly endemic Chaco region of Bolivia.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics make them very useful as screening tests in distant sites; however, a positive result must be confirmed later in a laboratory by CST. The low sensitivity values obtained with RDT by different authors suggest that they would be useful only if used in parallel with a CST, rendering them less useful in the field [14][15][16]. Diagnosis sensitivity can be enhanced by performing tests simultaneously on a single sample.…”
mentioning
confidence: 99%